(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Titanium coated tungsten carbide (Ti-WC) drill bit was used for drilling on the carbon-carbon composites laminates. The drilling speed was varied between 1000 to 3000 rpm with different feed rate of the drill. With respect to the time, the thrust force exerted on the laminates and the torque induced were assessed through acoustic emission process. The delamination factor (Fd) has been determined from the top surface of the drill holes through scanning electron microscope (SEM) images. The results obtained from the test specimen depending on the variation of the feed rate and the speed of the drill were discussed in detail.Â